2005
DOI: 10.1373/clinchem.2004.041350
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Adiponectin and Plasma Fatty Acid Profile

Abstract: Background:The amount and type of fat in the diet influence the development of obesity and related inflammatory activity. Knowledge of the possible influence of dietary habits on circulating adiponectin, a molecule with putative antiinflammatory properties, may be helpful in preventing atherosclerosis and type 2 diabetes. Methods: The association between dietary fat, as inferred from plasma fatty acid composition (gas-liquid chromatography), and circulating adiponectin (RIA) was evaluated in 116 healthy indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 40 publications
8
59
0
6
Order By: Relevance
“…46,47 In healthy humans, dietary saturated fat intake correlated negatively with circulating adiponectin, whereas omega-3 fatty acids were positively associated with this adipokine. 48 In conclusion, we confirmed that hypoadiponectinemia is an early finding in NASH, being detectable long before overt diabetes and overall or central obesity appear, and which correlates with the severity of liver histology. We provided evidence of an additional mechanism potentially linking adiponectin and NASH, postprandial lipid metabolism, and found a strikingly different postprandial adiponectin response between our patients and healthy controls, which may promote liver fat accumulation and insulin resistance in NASH.…”
Section: Discussionsupporting
confidence: 78%
“…46,47 In healthy humans, dietary saturated fat intake correlated negatively with circulating adiponectin, whereas omega-3 fatty acids were positively associated with this adipokine. 48 In conclusion, we confirmed that hypoadiponectinemia is an early finding in NASH, being detectable long before overt diabetes and overall or central obesity appear, and which correlates with the severity of liver histology. We provided evidence of an additional mechanism potentially linking adiponectin and NASH, postprandial lipid metabolism, and found a strikingly different postprandial adiponectin response between our patients and healthy controls, which may promote liver fat accumulation and insulin resistance in NASH.…”
Section: Discussionsupporting
confidence: 78%
“…Since EPA and DHA in humans were able to prevent but not reverse insulin resistance [3], it should be established whether the failure of dietary EPA and DHA to reverse type 2 diabetes is due to an inability to sufficiently induce adiponectin. Interestingly, an association between circulating adiponectin and plasma n-3 PUFA, and DHA in particular, was recently found in healthy humans [11].…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, an association between circulating adiponectin and plasma n-3 PUFA was recently found in healthy humans [23]. Based on this evidence, it has been hypothesised that possible protective effects of EPA and DHA may involve induction of adiponectin.…”
Section: Introductionmentioning
confidence: 92%